Grounding the Content of the Qur'an Surah Al-Fatihah in Everyday Life as a Form of Living Religion - Malik, Nida Husna Abdul (Jurnal Iman dan Spiritualitas, 2024)
This article presents a literature review of the book by Mary Pat Fisher and Robin Rinehart that discusses the concept of Living Religion and its application in everyday life, with a focus on Surah Al-Fatihah in the Qur'an. Surah Al-Fatihah, as a fundamental part of Islamic teachings, has a very deep and broad meaning, not only as a prayer in ritual worship but also as a moral and spiritual guideline in human interaction with God and others. This article explores how the values contained in Surah Al-Fatihah can be grounded in everyday life as part of a living religious practice. By applying the principles of Surah Al-Fatihah in everyday life, Muslims can face life's challenges more wisely and meaningfully. This discussion also raises the relevance of the concept of Living Religion in the modern pluralistic and dynamic world, where religious teachings need to be adapted to remain relevant and provide solutions to social and personal life problems. This article is expected to provide insight into the development of a more contextual and applicable understanding of religion, as well as encourage the application of religious values in everyday life that is more meaningful. Contribution: The discussion extends to the concept of Living Religion within a pluralistic and dynamic world, addressing the necessity for religious teachings to evolve and remain applicable to contemporary social issues. This perspective encourages interfaith dialogue and understanding in increasingly diverse societies.